Relation between maximum plantar pressure distribution and clubhead speed in amateur golfers - Pataky , T. C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Disagreements exist regarding the manner in which weight should be dynamically shared both within- and between-feet to generate maximal golf clubhead speed. The purpose of this study was test the null hypothesis that maximum plantar pressure (PP) distributions do not correlate with clubhead speed. Thirty-two amateur golfers (handicaps: 2.7-25) performed 10 swings with a driver. Clubhead speed was measured using a ball-flight monitor and PP distributions were recorded using an insole system. Results showed a significant positive correlation between lateral forefoot PP and clubhead speed (p=0.024) in the target-foot (the foot closest to the target), and this effect was independent of body mass (p=0.039). In contrast, medial PP tended to be negatively correlated with clubhead speed. This suggests that target-foot loading location may be as important as loading itself for maximizing clubhead speed.